18F-FDG PET/CT Evaluation of Ceritinib Therapy in Metastatic ALK-Positive Non–small Cell Lung Cancer. (November 2016) - Dejust, Sebastien; Morland, David; Fabre, Guillaume; Prevost, Alain; Papathanassiou, Dimitri
Abstract : Abstract: Anaplastic lymphoma kinase (ALK)–positive non–small cell lung cancers (NSCLC) account for 3% to 7% of all NSCLC and require a standard treatment by crizotinib. However, crizotinib resistance is frequent within the first 12 months of treatment. Ceritinib is a novel tyrosine kinase inhibitor of ALK recently introduced in France for metastatic or locally advanced crizotinib-resistant ALK NSCLC. We report the first use of ceritinib in our institution with a spectacular tumoral response after only 3 months of treatment. This case demonstrates the major role of 18 F-FDG PET/CT for monitoring the effectiveness of this new treatment.